From soccer to futsal: Brazilian elite level men players' career pathways. (4th July 2021) - Marques, Renato Francisco Rodrigues; Schubring, Astrid; Barker-Ruchti, Natalie; Nunomura, Myrian; Menezes, Rafael Pombo
ABSTRACT: Many Brazilian boys dream of a professional soccer career. During adolescence, however, many players move into futsal, a popular, less professionalized counterpart to soccer. To study players' investment in a futsal career, this article aimed to understand how childhood socialization relates to players' career development; to reconstruct the pathways players developed to become elite futsal athletes; and to identify reasons that led players to move from soccer to futsal. Semi-structured interviews with 18 Brazilian national team futsal players provided data. Bourdieu's Theory of Social Fields helped to understand players' investment in futsal. The results show that players experienced a fruitful social context and familial socialization that facilitated 'ball-kicking capitals'; developed a habitus that better matched the futsal than the soccer subfield; and delegitimized soccer as a suitable environment to participate in. We conclude with critical implications for futsal and soccer stakeholders aiming to maintain/create attractive career environments in times of increasing professionalism.